2018
DOI: 10.1080/00498254.2018.1453100
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and metabolism of the G protein-coupled receptor 40 agonist TAK-875 (fasiglifam) in rats, dogs, and humans

Abstract: The absorption, distribution, metabolism, and excretion of fasiglifam were investigated in rats, dogs, and humans. The absolute oral bioavailability of fasiglifam was high in all species (>76.0%). After oral administration of [C]fasiglifam, the administered radioactivity was quantitatively recovered and the major route of excretion of radioactivity was via feces in all species. Fasiglifam was a major component in the plasma and feces in all species. Its oxidative metabolite (M-I) was observed as a minor metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…In a repeated-dosing study of N-STZ-1.5 rats, 1 mg/kg SCO-267 (C max 5 139 ng/ml; AUC 0-24 h 5 626 ng•h/ml) was more effective in improving glucose tolerance than 10 mg/kg fasiglifam (C max 5 39.8 mg/ml; AUC 0-24 h 5 255 mg•h/ml). Plasma protein binding of SCO-267 was similar across species (99.6%-99.7%), and fasiglifam showed similar plasma protein binding across species (.99.4% for fasiglifam (Kogame et al, 2019)). With the clinically effective exposure of 50 mg fasiglifam (C max 5 5.3 mg/ml; AUC 0-24 h 5 100.3 mg•h/ml) (Leifke et al, 2012), SCO-267 may be effective in improving glucose control in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 88%
“…In a repeated-dosing study of N-STZ-1.5 rats, 1 mg/kg SCO-267 (C max 5 139 ng/ml; AUC 0-24 h 5 626 ng•h/ml) was more effective in improving glucose tolerance than 10 mg/kg fasiglifam (C max 5 39.8 mg/ml; AUC 0-24 h 5 255 mg•h/ml). Plasma protein binding of SCO-267 was similar across species (99.6%-99.7%), and fasiglifam showed similar plasma protein binding across species (.99.4% for fasiglifam (Kogame et al, 2019)). With the clinically effective exposure of 50 mg fasiglifam (C max 5 5.3 mg/ml; AUC 0-24 h 5 100.3 mg•h/ml) (Leifke et al, 2012), SCO-267 may be effective in improving glucose control in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 88%
“…In general clear species differences were seen in the metabolic profiles (Table S1;Figure and the supplementary material, interspecies comparison of metabolic profiles) of liver microsomes and hepatocytes of human and animal species suggested that it was not easy to find meaningful toxicological species or animal models in case of TAK875 1 . Nevertheless Kogame et al found that disposition and metabolism of fasiglifam is similar between human, rats, and dogs. However, we found in liver microsomes with cofactor NADPH the following differences have been observed for the oxidative pathways in human, rat, and dog.…”
Section: Resultsmentioning
confidence: 99%
“…It could occur in vivo but cannot be proven as a human in vivo liver data are not accessible. Kogame et al have recently published the in vivo human metabolism of TAK875 in comparison with animal species after single dose administration. TAK875‐GlcA 4 was a minor metabolite in plasma, urine, and feces of human, as well in dog and rat (0.1%‐2% overall).…”
Section: Resultsmentioning
confidence: 99%
“…As the concentrations of metabolites were higher than in incubation samples, bile was used for metabolite identification. Although a detailed metabolism study has been reported recently using a radiolabeled compound, four new metabolites (M2, M3, M4 and M8) were identified, which further demonstrated the capability of UHPLC‐Q Exactive Orbitrap‐MS combined with Metwork software in metabolite identification. Under the current conditions, a total of eight metabolites were detected and identified.…”
Section: Resultsmentioning
confidence: 89%